Pola Kemitraan Kebun Family Farm Hidroponik dengan PT Puspa Agro Farm Sukabumi - M. Fauzi M. Muttaqin; Ema Hilma Meilani; Endang Tri Astutiningsih (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2024)
The growth of the urban population has led to a shortage of agricultural land. This has led to an increase in urban agriculture, including hydroponics. The purpose of this research is to find out the partnership mechanism between hydroponic family farm and PT Puspa Agro Farm Sukabumi. This research uses descriptive analysis method found that the partnership between hydroponic family farm and PT Puspa Agro Farm is plasma core pattern. This pattern describes the assistance to hydroponic family farms from PT Puspa Agro farm. This is done to produce high quality plants and meet the criteria. The types of plants are pakcoy mustard, pagoda mustard, curly lettuce, and romaine lettuce for each plant. Family farms establish partnership relationships through the Inti-plasma mechanism. The partner company guides the production process of partner farmers so that they can provide quality vegetables in accordance with the SOPs that are applied. The partnership pattern between Family Farm and PT Puspa Agro is a core-plasma mechanism. The plants produced are pakcoy mustard, pagoda mustard, curly lettuce and roamine lettuce. The benefits of the nucleus-plasma partnership pattern are that it can improve in economic and technical terms. Family Farm plants are of high quality and can meet consumer criteria.